Sarcopenia is associated with insomnia in Japanese older adults: a cross-sectional study of data from the Nagasaki Islands study - Yuki Nagaura; Hideaki Kondo; Mako Nagayoshi; Takahiro Maeda (BMC Geriatrics, 2020)
Abstract Background Sarcopenia is associated with increased mortality among older adults. Sleep-related problems have been studied as factors related to sarcopenia. This study was conducted to determine the relationship between sleep-related problems and sarcopenia among Japanese community-dwelling older adults using data from the Nagasaki Islands Study. Methods This cross-sectional study analyzed data collected from 2017 to 2018. A total of 1592 older adults (575 men, 36.1%) aged 65 years or older participated. Sarcopenia was evaluated using the skeletal muscle mass index and grasp powers based on the criteria of the Asian Working Group for Sarcopenia. Odds ratios for sarcopenia were calculated using logistic regression analysis. Furthermore, subgroup analysis was performed based on the following tertiles of age: 65–70 years, 71–78 years, and 79–98 years. Results The number of participants with sarcopenia was 238 (14.9%). The median age of participants in the sarcopenia group (80 years; interquartile range: 74–84) was significantly higher than in the non-sarcopenia group (73 years; interquartile range 69–79; P <  0.001). In the sarcopenia group, 70.9% of participants had difficulty initiating and/or maintaining sleep, sleep duration tended to be longer (P <  0.001), and 33.3% of participants’ sleep duration was over 9 h. In a logistic regression analysis for sarcopenia, advancing age was the most prominent factor, and the adjusted odds ratio (95% confidence interval) of facing difficulty initiating and/or maintaining sleep was 1.60 (1.14–2.25). Despite longer sleep duration being a significant factor in the univariable analysis, it was not significant in the multivariable analysis. In the logistic regression analysis for sarcopenia among older adults aged 79–98 years, the odds ratio (95% confidence interval) among women was significantly low at 0.53 (0.33–0.83). Conclusions Sarcopenia is associated with difficulty initiating and/or maintaining sleep among Japanese older adults. In sarcopenia control measures, sleep/wake disorders related to insomnia are required to be evaluated in detail to help inform nursing and medical policy.